Race and Sex Discrimination in Employment in Canada. Theories, Evidence and Policies - Jain, Harish (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
After having examined three theoritical approaches, the author presents public policy relating to race and sex discrimination in employment and analyzes 74 cases decided by the boards of enquiry and courts.